2022
DOI: 10.1177/08971900211065536
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pharmacist Interventions in Adult COVID-19 Patients Admitted to a Tertiary Care Hospital

Abstract: Background: Pharmacists are integral members of the multidisciplinary healthcare team who, with their skills, knowledge, and training, are well positioned to prevent, identify, and manage medication-related issues. Many published articles related to COVID-19 management have highlighted the important role of the pharmacists in assuring the safe, effective, and cost-effective use of medications. During such challenging times of COVID-19 pandemic that resulted in a high demand on medical resources and healthcare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(37 citation statements)
references
References 15 publications
2
29
0
6
Order By: Relevance
“…All studies were published in English and reported from February 2020 to January 2022. Three studies were prospective cohort studies [ 35 , 36 , 37 ], while the other four were retrospective observational studies [ 38 , 39 , 40 , 41 ]. Six studies were done in the inpatient setting [ 35 , 36 , 38 , 39 , 40 , 41 ], while one was done at a community pharmacy [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies were published in English and reported from February 2020 to January 2022. Three studies were prospective cohort studies [ 35 , 36 , 37 ], while the other four were retrospective observational studies [ 38 , 39 , 40 , 41 ]. Six studies were done in the inpatient setting [ 35 , 36 , 38 , 39 , 40 , 41 ], while one was done at a community pharmacy [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were prospective cohort studies [ 35 , 36 , 37 ], while the other four were retrospective observational studies [ 38 , 39 , 40 , 41 ]. Six studies were done in the inpatient setting [ 35 , 36 , 38 , 39 , 40 , 41 ], while one was done at a community pharmacy [ 37 ]. The studies’ sample sizes ranged from 22 [ 38 ] to 438 participants [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations